A study on health aspects of agate workers in Shakarpura- Khambat - Deepak B Sharma; Tushar A Patel; Amit Mohan Varshney (Indian Association of Preventive and Social Medicine, 2011)
Background: Workers working in the agate industries are dying of silicosis in regular interval for last 40 years in Khambhat. The agate industry is a household industry in the Khambhat region of Gujarat and its surrounding villages (1) . Objectives: To find the: 1. Age and sex distribution of studied agate workers 2. Occurrence of tuberculosis in agate workers and the number of times the TB treatment was taken 3. Number of deaths in the family because of agate work. 4. Health problems if any and type of health problems Methods: Cross sectional study involving 98 agate workers engaged in grinding work Results: One family member in 22 families had died because of working as agate grinder. 25(25.5%) cases were diagnosed of having tuberculosis and had taken AKT (DOTS). Out of these 25 persons who were diagnosed to be having TB, 1 person did not took the treatment, 15(60%) got this disease only once and had AKT (DOTS) once; whereas 6(24%) workers had taken AKT (DOTS) twice. On asking about the current health problem, 85(86.7%) replied that they were having one or the other health problems. 78(79.6%) replied that there remains bodily pain after work and 75(76.5%) said malaise is there. Conclusions: The condition of the agate workers is pitiable. They are working in the agate industry and putting their lives at risk for silicosis and silico-tuberculosis.